2018
DOI: 10.1016/j.ekir.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic Cognitive and Exercise Training May Preserve Cognitive Function

Abstract: IntroductionCognitive decline is common and increases mortality risk in hemodialysis patients. Intradialytic interventions like cognitive training (CT) and exercise training (ET) may preserve cognitive function.MethodsWe conducted a pilot randomized controlled trial of 20 hemodialysis patients to study the impact of 3 months of intradialytic CT (tablet-based brain games) (n = 7), ET (foot peddlers) (n = 6), or standard of care (SC) (n = 7) on cognitive function. Global cognitive function was measured by the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 62 publications
1
50
0
1
Order By: Relevance
“…Dialysis patients have had improved function through engaging in physical therapy, exercise, resistance training, and gymnastics . The benefits from physical activity include increased mobility, preserved cognitive function, handgrip strength, motivation to exercise, and independence in household activities …”
Section: Model Cga Program For Dialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dialysis patients have had improved function through engaging in physical therapy, exercise, resistance training, and gymnastics . The benefits from physical activity include increased mobility, preserved cognitive function, handgrip strength, motivation to exercise, and independence in household activities …”
Section: Model Cga Program For Dialysis Patientsmentioning
confidence: 99%
“…42,43 The benefits from physical activity include increased mobility, preserved cognitive function, handgrip strength, motivation to exercise, and independence in household activities. 44 Because CGA in nondialysis populations has proven to minimize functional decline, there is a promise that CGA can be effective in the dialysis setting; however, we must first address important challenges to the implementation of CGA in this population. First, we must identify which patients are most likely to benefit from CGA.…”
Section: Assessment Program For D Ialysis Patientsmentioning
confidence: 99%
“…Most recently, two pilot studies assessed the impact of different types of intradialytic exercise on cognitive function . One pilot randomized controlled trail of 30 adult HD patients aged 18 years and older assessed the impact of 4 months of intradialytic cycling for aerobic exercise on cerebral blood flow and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Another pilot randomized controlled trial of 20 HD patients of all ages assessed the impact of 3 months of intradialytic CT (tablet‐based brain games) (N = 7), ET (foot peddlers) (N = 6), or standard of care (SC) (N = 7) on measured cognitive function using the 3MS and TMTA/B . Patients with SC experienced decline in psychomotor speed and executive function by 3 months of follow‐up; this decline was not seen among those with CT or ET.…”
Section: Introductionmentioning
confidence: 99%
“…9 A randomized, 3-month, controlled trial in 20 HD patients found that intradialytic use of tablet based brain games or exercise training with foot peddlers was associated with less cognitive decline in psychomotor speed and executive function than was seen in HD patients not so treated. 10…”
mentioning
confidence: 99%